2019
DOI: 10.1016/j.mayocpiqo.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Hospital-Wide CIWA-Ar Protocol for Management of Alcohol Withdrawal Syndrome

Abstract: Objective To determine if a hospital-wide symptom-based alcohol withdrawal protocol may result in significant clinical improvements to patient outcomes, safety, and hospital efficiency. Methods Retrospective/prospective cohort study between January 1, 2016 and December 31, 2016 (pre-protocol), and between March 1, 2017 and August 7, July 2017 (post-protocol). Pre-protocol patients were identified retrospectively using International Classification of Diseases, 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, our data cannot allow conclusions about the effectiveness of specific treatments on patient outcomes, highlighting the need for further trials. Interestingly, a recent study reported that the implementation of a hospital-wide protocol for the management of AWS resulted in significant improvements in quality of care, decreased the need for ICU admission and the rate of intubation, reduced hospital length of stay, and was cost-savings [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our data cannot allow conclusions about the effectiveness of specific treatments on patient outcomes, highlighting the need for further trials. Interestingly, a recent study reported that the implementation of a hospital-wide protocol for the management of AWS resulted in significant improvements in quality of care, decreased the need for ICU admission and the rate of intubation, reduced hospital length of stay, and was cost-savings [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in AWS management have established the superior effectiveness of symptom-triggered AWS protocols over fixed-dose tapering (or provider preference) in reducing AWS-related complications including DT, need for intubation, and escalation in care to an IMU or ICU. [14][15][16] Other studies have also demonstrated the effectiveness of symptom-driven approaches to decrease the length of hospitalization, 15,17,18 lower the required benzodiazepine exposure necessary to treat AWS, 7,12,15,[17][18][19][20][21][22][23][24][25][26][27][28] and reduce the duration of treatment with benzodiazepine sedation. 7,12,[22][23][24][25][26][27]29 Although there are other effective validated indices described in the literature, 29 the CIWA-ar remains one of the most widely accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the use of protocolized approaches has been recommended and put into practice primarily in academic medical centers . Large-scale outcomes studies including multiple therapies in community-based practice settings remain poorly described …”
Section: Discussionmentioning
confidence: 99%
“…21 Large-scale outcomes studies including multiple therapies in community-based practice settings remain poorly described. 43 Based on a multidisciplinary collaboration among diverse clinical specialties, the KPNC BZD-S order set contained a bundle of features, including educational information on AWS timing, a severity scale, thiamine dosing, several adjunctive agents, and reduced BZD dosing scales. The use of AWS adjunctive agents increased with a concurrent decrease in use and dose of BZDs.…”
Section: Before Implementationmentioning
confidence: 99%